Kepemimpinan Kepala Sekolah yang Efektif Kunci Meningkatkan Kinerja Guru dan Kualitas Pendidikan - Faizah, Nurul; Burhanuddin, Burhanuddin; Sumarsono, Raden Bambang (Proceedings Series of Educational Studies, 2024)
Abstract : Headmasters have an important role in improving the quality of education. There are five competencies that headmasters must have, including personality, managerial, entrepreneurial, supervisory, and social competencies. In practice, headmasters are limited to structural positions that run the bureaucratic system without understanding their roles and functions properly. This research uses a systematic literature review with meta-analysis. The data in this study used research articles, proceedings, and books to analyze effective headmaster leadership. The results showed that headmaster leadership can improve teacher performance by improving student competence and performance, thus improving the quality of education. Effective headmaster leadership can motivate student engagement in the learning process, which will improve student achievement. Headmasters are not only top managers but also administrators and perform management functions to motivate and coach teachers in improving their professional, pedagogical, personality, and social competencies. An effective headmaster will realize the vision and mission of the school and make continuous improvements.Abstrak : Kepala sekolah memiliki peran penting dalam meningkatkan kualitas pendidikan. Kompetensi yang harus dimiliki kepala sekolah ada lima, antara lain kompetensi kepribadian, manajerial, kewirausahaan, supervisi, dan sosial. Dalam pelaksanaannya, kepala sekolah sebatas jabatan struktural yang menjalan sistem birokrasi, tanpa memahami peran dan fungsinya dengan baik. Penelitian ini menggunakan systematic literature review dengan analisis meta. Data dalam penelitian ini menggunakan artikel penelitian, prosiding, dan buku untuk menganalisis kepemimpinan kepala sekolah yang efektif. Hasil penelitian menunjukkan kepemimpinan kepala sekolah dapat meningkatkan kinerja guru dalam meningkatkan kompetensi dan kinerja siswa sehingga meningkatkan kualitas pendidikan. Kepemimpinan kepala sekolah yang efektif dapat memotivasi keterlibatan siswa dalam proses pembelajaran yang akan meningkatkan prestasi siswa. Kepala sekolah tidak hanya sebagai top manajer, tetapi juga sebagai administrator dan menjalankan fungsi-fungsi manajemen untuk memotivasi dan membina guru dalam meningkatkan kompetensi profesional, pedagogi, kepribadian, dan sosial yang. Kepala sekolah yang efektif akan mewujudkan visi dan misi sekolah dan melakukan perbaikan secara berkelanjutan.